(untitled) (Journal of the Bangladesh Agricultural University, 2026)
The aim of this experiment was to evaluate the effect of Saccharomyces cerevisiae fermented commercial moist feed (pellet) on the growth performance of broiler. The feeding trial was conducted for 35 days where commercial pellet feed was fermented for 48h at room temperature (26-28 Degree Celsius) with 2% S. cerevisiae and 50% moisture content. About 150-day old Indian River commercial broiler chicks were allotted for the experiment where first week were offered commercial pre-starter diet for adaptation. From age 8, the chicks were divided into five dietary treatment group (30 chicks each) with three replication (10 chicks each). The dietary treatments group were 1. Commercial Dry Feed (CDF) 2. Commercial Moist Feed (CMF) 3. Yeast added Commercial Dry Feed (Y-CDF) 4. Yeast added Commercial Moist Feed (Y-CMF) and 5. Yeast Fermented Commercial Moist Feed (YF-CMF), respectively. Maximum live weight gain was recorded in CMF (1867g) followed by 1665, 1598, 1583 and 1542g in Y-CMF, CDF, Y-CDF, YF-CMF groups, respectively. Feed intake was significantly increased in CMF (2472g) group compared to CDF group (2162g). After intaking commercial moist feed Feed Conversion Ratio (FCR) value was improved in CMF group (1.33) than CDF group (1.35). Fermentation of commercial pellet feed with yeast have no significant effect on growth performance of broiler. But moist pellet feed can increase feed intake that ultimately improve body weight gain and feed conversion ratio. J Bangladesh Agril Univ 24(1): 33–37, 2026